Facultative release from developmental constraints through polyphenism promotes adaptively flexible maturation - Rhebergen, Flor T.; Smallegange, Isabel M. (bioRxiv, 2021)
The timing of maturation, a critical fitness determinant, is influenced by developmental and energetic constraints, particularly when growth is poor in adverse conditions. Such constraints can be altered through developmental plasticity. Thus, in theory, plasticity in energetically costly sexually selected morphologies can promote life history flexibility in variable environments. We experimentally tested this hypothesis in bulb mites (Rhizoglyphus robini) that polyphenically develop as armed fighters with enlarged legs or as scramblers without modified legs. We found that (i) mites enter metamorphosis earlier if they develop as scramblers, (ii) mites accelerate the onset of metamorphosis when they sense resource limitation, and (iii) scrambler expression increases under increased competition for food, enabling males to mature early and escape juvenile mortality. We propose that life history plasticity can evolve through polyphenic release from sexually selected constraints, making the evolutionary dynamics of secondary sexual traits and life history traits, typically studied separately, interdependent.